Front Cover: Joint channel and power optimisation for multi‐user anti‐jamming communications: A dual mode Q‐learning approach. Issue 6 (6th April 2022) - Zhang, Xiaobo; Wang, Hai; Ruan, Lang; Xu, Yifan; Feng, Zhibin
Abstract : The cover image is based on the Research Article Joint Channel and Power Optimization for Multi‐user Antijamming Communications: A Dual Mode Q‐learning Approach by Xiaobo Zhang et al., https://doi.org/10.1049/cmu2.12339